Edible gas marbles stabilized with cocoa particles: understanding their behavior by tuning the edible liquid phase - Yagishita, Takuto; Fameau, Anne-Laure; Fujii, Syuji (Frontiers in Soft Matter, 2026)
IntroductionGas marbles have recently emerged as a new class of particle-stabilized gas–liquid systems. A gas marble consists of a single air bubble suspended in air and encapsulated by a thin liquid shell stabilized by solid particles, forming an air-in-liquid-in-air structure. Gas marbles can be generated using various edible particles, but their formation has so far been demonstrated almost exclusively in water, where only particles with intermediate wettability (moderately hydrophilic contact angles) lead to stable structures. Because liquid surface tension strongly influences the three-phase contact angle, expanding gas-marble formation beyond water requires understanding how the liquid phase governs gas marbles formation and stability.MethodsIn this work, we investigate the formation of gas marbles using cocoa particles and a wide range of edible liquids differing in surface tension and composition. We also systematically varied a model liquid phase from water/ethanol mixtures. Unlike previous studies that focused primarily on particle wettability in water-based systems, this work explicitly isolates and elucidates the role of the liquid phase in governing gas-marble formation.Results and discussionWe demonstrate that the three-phase contact angle can be tuned through liquid surface tension, enabling or inhibiting gas-marble formation. We show, for the first time, that stable cocoa-based gas marbles can be produced in a broad set of edible liquids, provided that the liquid surface tension remains sufficiently high (above 34 mN/m). These gas marbles exhibit notable robustness, including heat resistance and long-term stability. Overall, this study establishes clear criteria linking liquid surface tension, particle wettability, and gas-marble formation. These findings provide new physical insight into particle-stabilized gas–liquid interfaces beyond water systems and offer general formulation guidelines applicable across a wide range of edible and non-aqueous liquids.